Intelligent and Fuzzy Techniques : Smart and Innovative Solutions : Proceedings of the INFUS 2020 Conference, Istanbul, Turkey, July 21-23, 2020 /: Smart and Innovative Solutions : Proceedings of the INFUS 2020 Conference, Istanbul, Turkey, July 21-23, 2020. (2020) - Unknown
No abstract available